Karakteristik Kimia Dan Fisik Telur Burung Gosong Filipina (Megapodius cumingii) Dari Pulau Toroguso, Kabupaten Banggai, Sulawesi Tengah, Indonesia - I Made Budiarsa; Abdul Hakim Laenggeng; Samsurizal M Suleman; Amram Rede; Fatma Sandagang (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
This research was conducted to examine the physical characteristics, chemical composition of the eggs of the filipina gosong bird (Megapodius cumingii) obtained from nesting sites on the coast of Poat Island, Pagimana District, Banggai Regency, Central Sulawesi Province. Measurement of the physical characteristics of eggs (weight, diameter, length and egg index) were carried out at the Laboratory of Biology Study Program, Tadulako University. Besides, observation on egg color, shape and egg texture were also conducted. Measurements of water and fat content, protein, carbohydrates, ash, crude fiber and egg antioxidants (Proxymate analysis) were carried out at the Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Tadulako University. Amino acid analysis was carried out at the Integrated Laboratory of IPB by using HPLC (High Performance Liquid Chromatography). The results showed that the eggs of the Filipina charred bird had an oval shape with two shell colors, dark brown and light brown, and the texture was smooth. The average size of egg weight, length, diameter and egg index were 99.35 g, 7.31 cm, 5.5 cm and 72.43%, respectively. The results of the chemical analysis of filipino gosong eggs revealed that water and fat content, protein, carbohydrates, ash, crude fiber and egg antioxidants were 50.45%, 18.75%, 13.40%, 0.02%, 375.98% and 1.82% respectively. The result showed a higher protein content compared to fat content. The 17 types of amino acids included essential and non-essential amino acids. Glutamate was the highest concentration of 2.10%, while cysteine was the lowest concentration of 0.15%.